Creating the Profile of Participants in Mobility Activities in the Context of Erasmus+: Motivations, Perceptions, and Linguistic Needs - Kosma, Panagiotis; Parmaxi, Antigoni; Perifanou, Maria; Economides, Anastasios A.; Zaphiris, Panayiotis (My University, 2020)
With millions of participants, Erasmus+ is a unique opportunity to study, train, gain work experience or volunteer abroad. However, the lack of language competences is still one of the main barriers to participation in European education, training, and youth programs. This work aims to identify, analyze and present the language needs of the participants involved in mobility activities supported under Erasmus+ Key Action 1. Data were collected by means of an online questionnaire to identify all the necessary information regarding the language needs of the Erasmus+ KA1 Mobility participants as well as their motivations to participate in the mobility. Also, in order to collect additional information in creating a profile and identifying the linguistic needs of all the Erasmus+ participants, a series of semi-structured interviews with Erasmus+ key stakeholders and with Erasmus+ National Agency Officers was conducted. Findings from the online questionnaire and interviews revealed important considerations regarding the language needs of the participants, their motivations and expectations, as well as their challenges/difficulties during the mobility. The contribution of this manuscript is to provide a piece of new knowledge regarding the Erasmus+ KA1 participants profiles emphasizing the need for new strategies to facilitate further mobility in the context of Erasmus+ and enhance the idea of multilingualism across Europe.
Keywords: Erasmus; Higher education; Language learning; Mobility; Students